Role-Playing Computer Ethics: Designing and Evaluating the Privacy by Design (PbD) Simulation. - Shilton, Katie; Heidenblad, Donal; Porter, Adam; Winter, Susan; Kendig, Mary (Science & Engineering Ethics, 2020)
There is growing consensus that teaching computer ethics is important, but there is little consensus on how to do so. One unmet challenge is increasing the capacity of computing students to make decisions about the ethical challenges embedded in their technical work. This paper reports on the design, testing, and evaluation of an educational simulation to meet this challenge. The privacy by design simulation enables more relevant and effective computer ethics education by letting students experience and make decisions about common ethical challenges encountered in real-world work environments. This paper describes the process of incorporating empirical observations of ethical questions in computing into an online simulation and an in-person board game. We employed the Values at Play framework to transform empirical observations of design into a playable educational experience. First, we conducted qualitative research to discover when and how values levers—practices that encourage values discussions during technology development—occur during the design of new mobile applications. We then translated these findings into gameplay elements, including the goals, roles, and elements of surprise incorporated into a simulation. We ran the online simulation in five undergraduate computer and information science classes. Based on this experience, we created a more accessible board game, which we tested in two undergraduate classes and two professional workshops. We evaluated the effectiveness of both the online simulation and the board game using two methods: a pre/post-test of moral sensitivity based on the Defining Issues Test, and a questionnaire evaluating student experience. We found that converting real-world ethical challenges into a playable simulation increased student's reported interest in ethical issues in technology, and that students identified the role-playing activity as relevant to their technical coursework. This demonstrates that roleplaying can emphasize ethical decision-making as a relevant component of technical work.